PENERAPAN MODEL DISCOVERY LEARNING MELALUI LAWATAN SEJARAH UNTUK MENINGKATKAN KESADARAN SEJARAH DAN PRESTASI BELAJAR SISWA KELAS XI IPS 1 SMA NEGERI 1 WURYANTORO KABUPATEN WONOGIRI TAHUN 2015/2016 - Y., Yudaningsih; S., Sariyatun; Agung S., Leo (HISTORIKA, 2014)
This research aims to know whether the model application of Discovery Learning through visiting historical places can increase historical consciousness and learning acchievement of students  class XI IPS 1 SMANegeri 1 Wuryantoro, Wonogiri  in 2015/2016 academic year.This research method is a Classroom Action Research consists of three cycles with the stages of planning, implementation, observation, and reflection. This research subyect was class XI IPS 1 SMA Negeri Wuryantoro, Wonogiri as many as 26 students. The data collection technique used tests, observation, interviews, documentation, and questionnaires. The data analysis technique used the analysis techniques of descriptive qualitative.The results of the research showed based on test results, obtained historical conciousness of  students on the first cycle with an average value of 73.58 and classical passing grade 61,53%, the second cycle with an average value of 74.62 and classical passing grade 73,07%, and the third cycle  with an average of 77.45 and classical passing grade 92,31%. While the students’ learning achievements obtained  in the first cycle with an average value of 73.58 and classical passing grade 51,85%, the second cycle with an average value of 76.65 and classical passing grade 76,92%, the third cycle with the average value at 80.23 with the achievement of 88,40% passing grade . The application of  discovery learning model through visiting historical places can increase historical consciousness and learning achievement of students.